ALDOSTERONE-RENIN RATIO: ASSESSING APPROPRIATENESS IN DIAGNOSTIC PRACTICE - Khoo, Chong Moh; Pavai, Sthaneshwar; Ratnasingam , Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Clinical guidelines recommend the aldosterone-renin ratio (ARR) as a screening tool for primary aldosteronism (PA); however, results may be influenced by pre-analytical factors such as posture, timing, salt intake, and medications. METHODOLOGY We conducted a retrospective evaluation of ARR requests at University Malaya Medical Centre from August 2022 to August 2024. The study aimed to determine testing indications, review interfering medications, and assess test outcomes using data extracted from the laboratory and hospital information systems (LIS and HIS). RESULT Out of 882 ARR cases, 428 were reviewed. Excluded cases included those with patients aged over 70 or under 16, tests taken outside UMMC, incomplete data, and patients who chose follow-up elsewhere or underwent 4-hour post-saline suppression tests. The cohort consisted of 47.4% females (203) and 52.6% males (225). Confirmed primary aldosteronism (PA) was identified in 13.1% of ARR cases on two antihypertensives, 9.6% on three, and 10.5% on four or more antihypertensives, compared to 0.9% in those not on treatment. PA was also more frequent among those with adrenal incidentalomas (10.1% vs. 4.3%) and those with hypokalemia (20.0% vs. 1.5%). A total of 333 ARR tests were performed in patients taking concomitant medications known to interfere with ARR results. Additionally, 113 ARR tests (26.4%) were performed without concomitant potassium measurements, among which 4 cases with confirmed PA were identified. While ARR testing is recommended to be performed in the morning, this protocol was not consistently followed in our cohort. Of the 428 ARR tests conducted, 24 (5.6%) were confirmed to have primary aldosteronism (PA). CONCLUSION Our findings highlight the variability in ARR testing practices, particularly regarding the timing of tests and the influence of interfering medications. The results underscore the importance of adhering to clinical guidelines to optimize the diagnostic accuracy of ARR testing for primary aldosteronism.